2015
DOI: 10.1002/bjs.9740
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of sacral nerve stimulation for faecal incontinence

Abstract: SNS remains an effective treatment for FI in the long term for approximately half of the patients starting therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
3
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 38 publications
10
76
3
5
Order By: Relevance
“…explantations rates have been reported to vary from 10% to 24%, most commonly because of loss of efficacy. 13,14,19 Based on explantation rates in the literature, the causes for explantation in the current study are comparable with rates and indications reported previously in other studies. Reimplantation may be an option in these patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…explantations rates have been reported to vary from 10% to 24%, most commonly because of loss of efficacy. 13,14,19 Based on explantation rates in the literature, the causes for explantation in the current study are comparable with rates and indications reported previously in other studies. Reimplantation may be an option in these patients.…”
Section: Discussionsupporting
confidence: 88%
“…the remaining patients had replacement of the lead alone. in assessing the baseline characteristics of each group, the median CCf-fis was found to be significantly higher preoperatively in the reimplantation group as compared with the index implantation controls (index implantation: 17 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20]; reimplantation: 19 (range, [12][13][14][15][16][17][18][19][20]; p = 0.002). in addition, the postoperative median CCf-fis was found to be significantly higher in the reimplantation group (index implantation: 7 (range, 0-20); reimplantation: 12 (range, 3-20) p = 0.028).…”
Section: Resultsmentioning
confidence: 99%
“…A common method defining success after SNS is a weekly reduction in frequency of major incontinence episodes by at least 50%. Using these criteria, the European SNS Outcome Study Group found long‐term success rates in 71.3% of patients, and full continence (no episodes of major incontinence) in 50.0% . However, using quantitative continence scoring systems, ‘full continence’ is regarded as St Mark's continence score of zero, which is uncommonly achieved with any procedure for faecal incontinence and we feel that quantitative scoring more accurately reflects the true definition of continence which includes involuntary soiling, urgency and flatus incontinence.…”
Section: Discussionmentioning
confidence: 93%
“…Sacral nerve stimulation (SNS) has redefined the treatment algorithm for faecal incontinence . One attraction of the procedure is the ability to do a temporary trial of nerve stimulation (peripheral nerve evaluation, PNE) to assess whether long‐term stimulation is likely to be successful, with 65–90% of PNE cases showing improvement and progressing to a permanent stimulator .…”
Section: Introductionmentioning
confidence: 99%
“…Sacral nerve modulation has been shown to be effective for the treatment of severe FI when conservative measures have failed . It has become nowadays a standard treatment for this condition.…”
Section: Discussionmentioning
confidence: 99%